Defendant’s actions to delay court proceedings and the implementation of efficient court proceedings - Pisz, Łukasz (Prawo Kanoniczne, 2024)
The faster a modern person achieves their goals, the more satisfied they are. A similar pattern can be observed in court proceedings. A person who brings a case to court in accordance with the law can expect their case to be heard quickly and fairly. However, circumstances that arise during the proceedings may have the opposite effect to that expected. The actions of the defendant may lead to delays in the proceedings. Therefore, the legislator sets procedural deadlines that oblige both the judge and the parties to the proceedings to take certain necessary actions. If the parties fail to act within the time limit set by law or by the judge, the judge presiding over the proceedings may, in accordance with the law, take further procedural steps. Such action by the judge is an action that affects the efficient conduct of the court proceedings.